Design and implementation of a smart home system with two levels of security based on IoT technology - Mohammed Murad; Oguz Bayat; Hamzah M. Marhoon (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Besides the development of technology in recent years, there has been an effective tendency to construct smart cities and homes. Whereas the smart home control system components can be incorporated with the existing home appliances to eliminate the need for human intervention, save electricity, protect homes from accidents as well as the theft, and provide home residents with comfort. This work comprises the utilising of the internet of things (IoT) technology to build the proposed design for the smart home. The proposed design includes many subsystems as well as several types of sensors, such as the passive infrared (PIR) sensor, the gas sensor, the soil moisture sensor, the water level sensor, the temperature sensor, the light dependent resistance (LDR), and the flame sensor. Each sensor will be connected to the Arduino Nano for the data processing purpose, after which the Arduino Nano will be connected to the NodeMCU module via the digital pins to implement the IoT subsystem. The proposed system also includes a smart garage gate based on Bluetooth HC-05 module with a specially programmed android app.